Prevalence and Associated Factors of Low Birth Weight among Term Newborns in Dilla Town, Southern Ethiopia - Tsegaye Mehare; Yewbmirt Sharew (Hindawi Limited, 2020)
Introduction. Birth weight has emerged as the pointer of infant wellbeing and the fundamental focus of infant health policy. Low birth weight predisposes newborns to loads of health disarray like underweight, stunting, hypoglycemia, hypothermia, mental retardation, physical, and neurodevelopment problems which results in high rates of morbidity and mortality. This study aimed to assess the prevalence and associated factors of low birth weights in term newborns. Objective. This study designed to assess the prevalence and associated factors of low birth weight among term newborns in Dilla town, Southern Ethiopia. Materials and Methods. Institutional based cross-sectional study design was used on 472 term newborns. The study setting includes three health centers (Dilla, Wallemi, and Tumetecha) within Dilla town and Dilla University referral hospital from September 1, 2018, to January 30, 2019. The study subjects were mothers with term newborns delivered in the above institutions and those delivered at home and received care within the first 24 hours after delivery in the above health care settings. Results. A total of 161 (34.1%) of the term newborns were low birth weight. Divorced mothers, rural residents, maternal age <20 years old, unwanted and unintended pregnancy, no ANC follow-up, no dietary counsel, no foliate supplementation, and cigarette smoking have shown an association with low birth weight of neonates. Conclusions. Even though the method of sampling used in this study has its confines, the prevalence of low birth weight in this study was higher than the estimate in Ethiopia. Therefore, it is recommended that special attention should be given to pregnant mothers to get adequate rest, additional diet, and antenatal services available and accessible to all pregnant women.